Systematic review of the impact of the COVID-19 pandemic on suicidal behaviour amongst health and social care workers across the world - Chukwudi Okolie (Journal of Affective Disorders Reports, 2021)
BackgroundThe COVID-19 pandemic has had an impact on the mental health of healthcare and social care workers, and its potential effect on suicidal thoughts and behaviour is of particular concern.MethodsThis systematic review identified and appraised the published literature that has reported on the impact of COVID-19 on suicidal thoughts and behaviour and self-harm amongst healthcare and social care workers worldwide up to May 31, 2021.ResultsOut of 37 potentially relevant papers identified, ten met our eligibility criteria. Our review has highlighted that the impact of COVID-19 has varied as a function of setting, working relationships, occupational roles, and psychiatric comorbidities.LimitationsThere have been no completed cohort studies comparing pre- and post-pandemic suicidal thoughts and behaviours. It is possible some papers may have been missed in the search.ConclusionsThe current quality of evidence pertaining to suicidal behaviour in healthcare workers is poor, and evidence is entirely absent for those working in social care. The clinical relevance of this work is to bring attention to what evidence exists, and to encourage, in practice, proactive approaches to interventions for improving healthcare and social care worker mental health.